2016
DOI: 10.3382/ps/pew071
|View full text |Cite
|
Sign up to set email alerts
|

Incubation temperature alters thermal preference and response to heat stress of broiler chickens along the rearing phase

Abstract: The current study aimed to investigate whether embryonic temperature manipulation may alter thermal preference throughout the rearing phase of broiler chickens and how this manipulation may affect response to thermal challenge, metabolism, growth rate and feed intake rate. Eggs were exposed to a constant incubation temperature [machine temperatures: 36°C (Low), 37.5°C (Control), and 39°C (High); eggshell temperature of 37.4 ± 0.08°C, 37.8 ± 0.15°C, and 38.8 ± 0.33°C, respectively] from d 13 till hatching. Low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…For example, chickens that are exposed to a short cold challenge exactly during the HPT and HPA axis development in the egg are better heat-producers after hatching and later in life while in contrast, chickens exposed to similar short-duration d heat challenges prenatally cope better in higher ambient temperatures later in life (Kamanli et al, 2015;Loyau et al, 2015;Morita et al, 2016;Piestun et al, 2009;Piestun et al, 2008a;Piestun et al, 2008b;Piestun et al, 2015;Shinder et al, 2009;Yahav et al, 2004). For non-domesticated species, Nord & Nilsson (2011) and DuRant et al (2011), found that blue tits and wood ducks (Aix sponsa) that were incubated in cold temperature throughout the incubation period had higher metabolic rate close to independence, which was interpreted in the same wayi.e.…”
Section: Epigenetic Adaptationmentioning
confidence: 99%
“…For example, chickens that are exposed to a short cold challenge exactly during the HPT and HPA axis development in the egg are better heat-producers after hatching and later in life while in contrast, chickens exposed to similar short-duration d heat challenges prenatally cope better in higher ambient temperatures later in life (Kamanli et al, 2015;Loyau et al, 2015;Morita et al, 2016;Piestun et al, 2009;Piestun et al, 2008a;Piestun et al, 2008b;Piestun et al, 2015;Shinder et al, 2009;Yahav et al, 2004). For non-domesticated species, Nord & Nilsson (2011) and DuRant et al (2011), found that blue tits and wood ducks (Aix sponsa) that were incubated in cold temperature throughout the incubation period had higher metabolic rate close to independence, which was interpreted in the same wayi.e.…”
Section: Epigenetic Adaptationmentioning
confidence: 99%
“…Consistent with current study, Al-Zhgoul et al (2013) stated that a high temperature (38.8º C) for 6 h during d 10 to 18 of incubation increased T3 and T4 concentrations in 3 days old broiler chickens. Morita et al (2016) showed the non-significant increase in T4 level at hatch by applying high incubation temperature (38.8 o C) from d 13 to hatch. In contrast to these results, various studies have reported that high incubation temperature caused decreased plasma concentrations of thyroid hormones (Piestun et al, 2009;Willemsen et al, 2010).…”
Section: High Eggshell Temperaturementioning
confidence: 91%
“…Temperature is a critical factor affecting embryonic development and growth. Numerous studies have investigated the effects of different incubation temperatures on improving thermotolerance and its consequences (Al-Zhgoul et al, 2013;Morita et al, 2016;Piestun, Halevy, & Yahav, 2009). High incubation temperatures can negatively affect hatchability (Sozcu & Ipek, 2015), chick quality (Willemsen et al, 2011), and post-hatch growth performance (Sozcu & Ipek, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Only chicks born from 477 to 492h of incubation were chosen for rearing, as they presented the hatching patterns established in the experimental design of this study in a short hatching window to avoid fasting effects. Then, 72 male chicks (hatched from 477 to 492h of incubation) from each treatment were housed in climatic chamber with automatic control of temperature and light period (light:dark = 22h:2h) [23], containing 16 boxes (1.5x 2.50 m, 18 chicks per box), kept at recommended temperature for the strain [28]. The temperature and relative humidity in the chamber were registered three times a day during the experimental period, and for this we used two digital thermo-hygrometers located at equidistant points of the chamber.…”
Section: Rearingmentioning
confidence: 99%
“…Lohmann chicks subjected to intermittent heat stress (4 hours/day at 40˚C) in the period between the 14 th to 18 th day of incubation prefer low ambient temperatures up to the 7 th day of life [22]. In previous studies, we found that broiler chicks from eggs incubated at high temperature (39˚C) from day 13 of incubation (fetal phase) have thinner and more vasculated skin, that may help chicks to have greater heat loss and to maintain body temperature, and prefer higher rearing temperature until the 21 st day of life compared to broilers from egg incubation at usual (37.5˚C) and cold (36˚C) temperature [23,24].…”
Section: Introductionmentioning
confidence: 99%